Evaluasi Perencanaan dan Pengadaan Kebutuhan Obat Terhadap Ketersediaan Obat di Apotek Cicaheum Farma - Anti Khaerunnisa; Moh. Rizky Adriansyah (Publikasi Indonesia, 2022)
The vacancy of drug supply in each health unit is a component of a complex problem. Therefore, an effective and efficient drug management is needed. One of the effective drug management processes is to ensure the availability of drugs, both in terms of the right types and quantities according to needs, so as to avoid drug shortages and excesses. This study aims to evaluate the process of planning and procurement of drugs at the CicaheumFarma Pharmacy. The research method used is descriptive qualitative research method with data collection techniques through interviews and checklists to the CicaheumFarma Pharmacy. Based on the research, it shows that the planning and procurement process at the CicaheumFarma Pharmacy has not gone well because the procurement process that has been running so far is only based on estimates of selling power, causing a shortage of drug supplies. The conclusion from interviews with the owner and employees as well as the results of the checklist to anticipate the occurrence of vacancies in drug supplies at the CicaheumFarma Pharmacy that the owner will change the planning and procurement process system for drugs to be better in the future.